2022
DOI: 10.52403/ijrr.20220861
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Organizational Culture on Employee Affective Commitment to Change with Employee Resilience and Employee Readiness to Change as Mediators

Abstract: Changes in the organizational environment (e.g. IT, covid-19, age of employees) are driving organizational change, including government organization. Several studies have shown that 70% of change programs fail to run with various causes. The role of humans as a factor that influences the success of organizational change is necessary to research employee commitment to change by looking at the factors that affect it. This study aims to analyze, interpret and evaluate resource management practices, especially abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Their results demonstrated the importance of these elements in boosting commitment by underlining the favorable direct effects of organizational culture and leadership style on organizational commitment. Additionally, Purwana and Clara (2022) examined how employee resilience and change readiness served as mediators between corporate culture and affective commitment to change among employees. Their study showed that, via employee readiness to change as a mediating variable, externally oriented company culture greatly influences employee affective commitment to change.…”
Section: Affective Commitment To Change Among Employees Organizationa...mentioning
confidence: 99%
“…Their results demonstrated the importance of these elements in boosting commitment by underlining the favorable direct effects of organizational culture and leadership style on organizational commitment. Additionally, Purwana and Clara (2022) examined how employee resilience and change readiness served as mediators between corporate culture and affective commitment to change among employees. Their study showed that, via employee readiness to change as a mediating variable, externally oriented company culture greatly influences employee affective commitment to change.…”
Section: Affective Commitment To Change Among Employees Organizationa...mentioning
confidence: 99%